(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
A fixed oscillating water column is a hollow structure open to the sea at its submerged part. The water column motion alternately compresses and decompresses the enclosed air above the inner free surface, which drives a self-rectifying air turbine. In 2003, Boccotti proposed the so-called U-OWC having in view the integration into breakwaters. In this configuration, the inner water is connected to the sea by a U-shaped duct whose opening faces upwards rather than sideways or downwards. This allows the OWC length to be extended (and the resonance frequency reduced) without placing the opening too deeply submerged where wave energy is attenuated by distance to the free-surface. An advantage of OWC converters is the capability to control or dissipate the excess energy available to the power take-off system in excessively energetic sea states. This is in general done by limiting the air turbine torque by controlling a by-pass air valve or a valve in series with the turbine. What is proposed here is to take advantage of the water column configuration to limit the energy absorbed from the waves in the more energetic sea states. This requires the tidal amplitude to be small as occurs in coastal areas like the Mediterranean Sea. The distance of the OWC opening to the mid-sea-level should be chosen such that, in the more energetic sea states, that opening is left uncovered by the troughs of the higher waves. This introduces a limitation to the energy absorbed in the more energetic sea states. This paper reports experiments with a 1:40th-scale U-OWC in a wave flume. The results show that limitations to the capture width ratio occurs in the more energetic wave systems.